Penguatan Kompetensi Complex Problem Solving Melalui Pembelajaran Keterlibatan di Era Masyarakat Digital - Hidayah, Yayuk; Trihastuti, Meiwatizal; Muttaqi, Nabila Ihza Nur; Suhono, Suhono (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2025)
Complex problem-solving skills are essential competencies for addressing the challenges of an ever-evolving digital society. This study aims to explore the enhancement of these skills through a community engagement approach. The research was conducted with students from Universitas Negeri Yogyakarta, specifically from the Civil Engineering and Planning Education, Electrical Engineering, Architecture, and Law departments, during the 2024 odd semester. A qualitative method was employed, utilizing interviews, participatory observations, and document analysis for data collection.The findings reveal that student participation in community-based programs, such as renewable energy technology development, eco-friendly architectural design, sustainable infrastructure, and digital law solutions, significantly improved critical thinking, multidimensional analysis, and cross-disciplinary collaboration skills. Engagement with the community broadened students' understanding of social, cultural, and technological contexts, fostering the creation of innovative and relevant solutions. The study recommends integrating community-based programs into the curriculum, fostering partnerships with local communities, and providing intensive training to support 21st-century competency development, aiming to produce adaptive and competitive graduates.